The Role of Strategic Audit Dimensions in Enhancing Institutional Performance - Fatima Abid Ali Sliman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The proposed research will focus on defining the effects of the strategic audit aspects instrengthening the institutional performance of the Iraqi General Cement Company. The research targetedfour important dimensions that are strategic position of the institution, the internal environment, theexternal environment, and the stakeholder, and how these dimensions would be associated with variousdimensions of performance such as learning and growth, internal operations and customer satisfaction,financial performance, and environmental performance. The research methodology employed adescriptive and analytical approach, utilizing statistical methods such as SPSS V.25 and AMOS V.23 totest the study's hypotheses. The findings indicated that both the external environment and the involvementof the stakeholders had the most significant positive impacts on both the financial and the environmentalperformance of the company, whereas the internal environment was found to have solid effects oninternal activities and on customer satisfaction. The average effect on learning and development was alsorecorded on the strategic position. The findings of the study indicated that as a way of sustaininginstitutional performance, a combined consideration of strategic alignment, overall institutional processadvancement and the partnership with stakeholders should be implemented.